Implementation of Fuzzy Logic on Recommendation Levels of Packaged Milk Based on Price and Nutritional Value - Qorie Rania; Chika Hayya Sabillah; Muhammad Faiz Assariy; Daffa Zulqisthi; Muhammad Afzaal Abimanyu; Anastasya Gabriella; Nurani Amaliatunnisa; Nurul Alfiani Dewi; Disty Isbiyanti Prananingrum; Aphisa Nahl Fitria; Mrr. Lukie Trianawati (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
The abundance of packaged milk products in the market requires consumers to consider several factors to obtain high-quality packaged milk at an affordable price. Milk demand in Indonesia showed a slight increase from 2019 to 2020, rising from 16.23 in 2019 to 16.27 in 2020. However, the average milk demand in Indonesia has remained fluctuating, largely due to the increasing prices of milk products on the market. This study aims to determine the recommendation level for packaged milk by considering both price and nutritional content. The method used in this research involves a mathematical assessment of milk products using fuzzy logic. The data for this study is derived from previous research on packaged milk samples as the observation objects. The results indicate that sample 16 is highly recommended due to its low price and very high nutritional content.